Lompatan Kemajuan Ull Dalam Usia Ke-70 - Darwin Harsono (Universitas Islam Indonesia, 2013)
The historical background of Indonesian Islamic University is very phenomenal thing especially for mapping of progress of Indonesia as afree country. Some of the founding of Ull are the leaders of the Republic of Indonesia. They ‘re the true statesmen who aimed to accelerate the development of the nation through education and politics. Than they iniciated to build an Islamic University (IIU ) in accordance with the need of musiim’ country especially and for the nation in general. IIU’s vision and mission shows up the goal of it and of course it’s Islam to be assured of making Islamic system of education based on Qur’an’s message namely ‘rahmatan IH’alamin - benevolence for Universe (Q 21:107). It will gives guaranty in the long run good output: high dedicated and integrated alumnies for glorifieng Islam and muslim’s people. For now on it’s the duty of IIU for preparing hard ware and soft ware taking a high role as a center of excellence, of IIU in ASEAN, sublimized the loss glory of Andalusian’ Islamic University.Key words: UII, Indonesia, vision, mission